Studi Penggunaan Sefalosporin Generasi Ketiga pada Pasien Pneumonia di Instalasi Rawat Inap Rumah Sakit Umum Haji Surabaya - Worotikan, Natania Imanuella; Hasmono, Didik; Kasih, Elisabeth; Ramdani, Dewi (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2019)
Pneumonia is an acute lung tissue infection caused by inflammation of the lung parenchyma and the presence of exudate compaction in lung tissue. Based on epidemiology, pneumonia can be differentiated into communityacquired pneumonia and health care-associated pneumonia. The HCAP category divided pneumonia into hospital acquired pneumonia and ventilator-associated pneumonia. This study aims to analyze the pattern of third generation cephalosporin use in pneumonia patients based on drug route of administration, dosage, frequency, interval and duration of drug usage, and laboratory data. This study was conducted retrospectively with time limited sampling method during the period of August 1, 2016 - August 31, 2017. The study was conducted in 31 patients with diagnosis of pneumonia undergoing hospitalization and received third generation cephalosporin antibiotic therapy at inpatient installation of RSU Haji Surabaya which traced through Medical Record. All samples were recorded on the data collection sheet, and then the data was recapitulated and analyzed. Based on the observation result, it was found that ceftriaxone with frequency and dose 2x1 g (iv) used as much as 41% (11 people), the combination between ceftriaxone 2x1 g (iv) with levofloxacin 1x1 g (iv) used as much as 22% (4 people). The longest use of third generation cephalosporin antibiotics was ceftriaxone (4-6 days) as much as 35% (12 people).